Development and Characterisation of Anti-Septic Cream Containing Turmeric, Aloe Vera Gel and Jatyadi Oil (International Journal of Ayurveda and Pharma Research, 2025)
The need of herbal medicines is increasing rapidly due to their fewer side effects. Herbal drugs constitute a major part in all the traditional system of medicine. Hence an attempt has been made to formulate and evaluate cream for its antiseptic activity against Propionic Bacteria. In this context, the study has been conducted to formulate polyherbal cream using turmeric, aloe vera extract and Jatyadi oil, all the extracts are obtained by using various extraction techniques such Maceration, Steam distillation and Soxhlet apparatus. Preliminary phytochemical screening was carried out for all the herbal extracts the final formulation was evaluated for different evaluation parameters. The formulation was evaluated for antiseptic activity against Propionic bacteria by MIC method.